Abiotic origin of the citric acid cycle intermediates - Mason McAnally; Jana Bocková; Andrew M. Turner; Nana Hara; Daria Mikhnova; Cornelia Meinert; Ralf I. Kaiser (Proceedings of the National Academy of Sciences, 2025)
The molecular framework for protometabolism—chemical reactions in a prebiotic environment preceding modern metabolism—has remained unknown in evolutionary biology. Mono-, di-, and tricarboxylic acids that comprise contemporary metabolism, such as the Krebs cycle, are of particular prebiotic relevance and are theorized to predate life on Earth. Researchers have struggled to unravel the molecular origins of respiration, with theories pointing toward abiotic origins later co-opted by the earliest living organisms; however, the molecular network of these molecules has remained elusive. Recent detections of carboxylic acids linked to the Krebs cycle on the Ryugu asteroid and Murchison meteorite rekindled interest in their extraterrestrial origins. Replicating conditions analogous to the environment of dense molecular clouds in laboratory simulation experiments, our work provides compelling evidence on the abiotic synthesis of the complete suite of biorelevant molecules central to the Krebs cycle. The opportunity for these biomolecules forming in deep space could provide molecular origins of protometabolism on early Earth and also provide the molecular feedstock to worlds beyond our own.